2015
DOI: 10.1136/jfprhc-2013-100833
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and awareness of human papillomavirus infection and cervical cancer screening results among reproductive-aged Georgian women

Abstract: More comprehensive public awareness campaigns should be developed to raise awareness about HPV screening and prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Additionally, it has been shown that the cell-mediated immune response cleared the majority of HPV infections within 1–2 year’s exposure [14]. Despite the fact that a number of seroprevalence studies have been conducted in resource-rich countries and some in resource-poor countries [1518], no such data appears to be available from the Arab world.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been shown that the cell-mediated immune response cleared the majority of HPV infections within 1–2 year’s exposure [14]. Despite the fact that a number of seroprevalence studies have been conducted in resource-rich countries and some in resource-poor countries [1518], no such data appears to be available from the Arab world.…”
Section: Introductionmentioning
confidence: 99%
“…Most Georgian interviewed women too pointed out televisions and print media are good methods of communications. The results view importance of developing and launch more comprehensive public outreach using media to increased knowledge and awareness about HPV (Butsashvili et al, 2015).…”
Section: Influencing Factorsmentioning
confidence: 99%